Valores e aprendizagem organizacionais: um estudo em uma organização não governamental - Mello, Samuel Ferreira de (2012)
This work has aimed the understanding between two constructs in Business area, organizational values and organizational learning, in the light of the members of a Non Governmental Organization in the city of Santa Maria. So, descriptive interviews were held, using the quantitative method to gather and analyze the data. The instrument to collect the data was divided in three parts. The first one aimed to understand the population profile; the second searched to identify the noticed organizational values, based on Oliveira and Tamayo (2004); and the third part sought to verify how is the learning process in the organization based on Goh and Richards (1997) and Angelim and Guimarães (2003). To analyze the data were realized tests in the organization population composed by 78 members. The correlation between de constructs was carried out, as well as the mean and the standard deviation. The study relevance stands on both concepts being active agents in the changing process, they are able to highlight the teams abilities, to set a shared vision, to clarify common objectives and to ensure the continuous learning process. The main results were the members in this organization prioritize the Autonomy and Fulfillment values, evidencing that challenges and possibility to be creative as well as competence and success are organizational values strongly present in the organization. In relation to learning, the dimensions Clarity of Mission and Purpose were considered at the top by the members, showing that the organization puts out clearly its mission, in which may facilitate to the members understand the possible ways to achieve the objectives. Finally, this research reveals a moderate correlation between the value Autonomy and the learning dimension Experimentation, and also between the value Concern for the Collective and the learning dimension Knowledge Transfer.